Genome-wide analysis of the acyl-coenzyme A synthetase family and their association with the formation of goat milk flavour - Zhang, Fuhong; Luo, Jun; Shi, Chenbo; Zhu, Lu; He, Qiuya; Tian, Huibin; Wu, Jiao; Zhao, Jianqing; Li, Cong (Frontiers in Genetics, 2022)
Goat milk is rich in fat and protein, thus, has high nutritional values and benefits human health. However, goaty flavour is a major concern that interferes with consumer acceptability of goat milk and the 4-alkyl-branched-chain fatty acids (vBCFAs) are the major substances relevant to the goaty flavour in goat milk. Previous research reported that the acyl-coenzyme A synthetases (ACSs) play a key role in the activation of fatty acids, which is a prerequisite for fatty acids entering anabolic and catabolic processes and highly involved in the regulation of vBCFAs metabolism. Although ACS genes have been identified in humans and mice, they have not been systematically characterized in goats. In this research, we performed genome-wide characterization of the ACS genes in goats, identifying that a total of 25 ACS genes (without ACSM2A) were obtained in the Capra hircus and each ACS protein contained the conserved AMP-binding domain. Phylogenetic analysis showed that out of the 25 genes, 21 belonged to the ACSS, ACSM, ACSL, ACSVL and ACSBG subfamilies. However, AACS, AASDH, ACSF and ACSF3 genes were not classified in the common evolutionary branch and belonged to the ACS superfamily. The genes in the same clade had similar conserved structures, motifs and protein domains. The expression analysis showed that the majority of ACS genes were expressed in multi tissues. The comparative analysis of expression patterns in non-lactation and lactation mammary glands of goat, sheep and cow indicated that ACSS2 and ACSF3 genes may participate in the formation mechanisms of goaty flavour in goat milk. In conclusion, current research provides important genomic resources and expression information for ACSs in goats, which will support further research on investigating the formation mechanisms of the goaty flavour in goat milk.